2023
DOI: 10.3390/ijms24021449
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Transmission and Antifungal Susceptibility Profile of Yeast Isolates from the Oral Cavity, Gut, and Breastmilk of Mother–Child Pairs in Early Life

Abstract: Yeast acquisition begins at birth; however, the contribution of the mother on yeast transmission to the offspring and associated resistance is yet to be clarified. The aim of this study was to explore the vertical transmission of yeasts and their antifungal susceptibility profile in early life. Oral, fecal, and breastmilk samples were collected from 73 mother–child pairs four to twelve weeks after delivery and cultured on Sabouraud dextrose agar with chloramphenicol. The isolates were identified by MALDI-TOF M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
2
1
0
Order By: Relevance
“…Moreover, infants in the C . albicans positive group showed a higher likelihood of having a documented history of oral thrush diagnosis and previous use of antifungal medications, aligning with the results reported by Azevedo et al [ 64 ]. Oral thrush is a common infection in early life, affecting 4%-15% of healthy children [ 65 , 66 ], with C .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, infants in the C . albicans positive group showed a higher likelihood of having a documented history of oral thrush diagnosis and previous use of antifungal medications, aligning with the results reported by Azevedo et al [ 64 ]. Oral thrush is a common infection in early life, affecting 4%-15% of healthy children [ 65 , 66 ], with C .…”
Section: Discussionsupporting
confidence: 90%
“…Further research is needed to clarify the relationship between feeding methods and Candida colonization in infants and children. Moreover, infants in the C. albicans positive group showed a higher likelihood of having a documented history of oral thrush diagnosis and previous use of antifungal medications, aligning with the results reported by Azevedo et al [64]. Oral thrush is a common infection in early life, affecting 4%-15% of healthy children [65,66], with C. albicans often being the opportunistic microorganism responsible for the infection [67].…”
Section: Plos Onesupporting
confidence: 85%
“…More recently, Ward et al (2018) reported that key body‐site‐specific taxa were impacted by birth mode. Azevedo et al (2023) demonstrated that vertical transmission of yeasts happens in early life and the role of the mother as a source of transmission of yeasts to the child. As vaginal yeast regularly occurs and is transmitted from the mother to neonate during delivery, we assumed that the H. pylori hosted by yeast also follows this transmission route.…”
Section: Introductionmentioning
confidence: 99%